Indian Stock Market Volatility and Economic Fundamentals : MIDAS Approach - Ashwani,; Sheera, Ved Pal (Indian Journal of Finance, 2018)
Since the onset of endogenous growth theory, financial development has remained a centre place among policymakers and academicians for its multifold roles in accumulation of productive assets in an economy. Parallelly, the capital market has also provided advantages to the stakeholders through diversification of risk, amelioration of liquidity risk, discovery of asset prices, etc. In this regard, numerous studies have tried to capture the dynamics of stock markets across countries and within countries. The literature mentioned that the macroeconomic fundamentals have varying roles in predicting the behaviour of stock markets. Most of the existing literature utilized the data set of comparable frequencies that is maximally available at the monthly level. However, the extent of volatility measurement of stock markets using high frequency data as of stock markets along with low frequency data as of macroeconomic indicators was overlooked in the Indian stock market. In this background, the present study took motivation to capture the roles of macroeconomic variables in explaining the volatility of the Indian stock market using the recently developed MIDAS GARCH approach. The study observed that macroeconomic variables such as exchange rate, money supply, treasury bills rate, along with the controlling variables of net foreign institutional investment and stock turnover ratio had predictable capacity for stock market volatility.